Pewarisan Trauma dan Konsep Ibu dalam Film Ali & Ratu-Ratu Queens: Analisis Teori Postmemory Marianne Hirsch - Putra, Jalu Norva Illa; Citrawati, Ni Putu Evi Wahyu (MIMESIS, 2023)
This research will look at the relationship between memory and literature, which is about the process of inheritance of memory. A film entitled Ali and The Ratu-ratu Queens was chosen to be the object of this research, which will look at the relationship between memory, trauma, and the process of inheritance. This study aims to determine the trauma of the other that is passed on to the self, its transmission process and also to identify the reconstruction of the trauma that is owned by the self. This paper will use a perspective of Postmemory theory from Marianne Hirsch. Postmemory is a theory that looks at the process of inheritance of trauma between generations. This theory will look at the process of Ali as second generation inheriting his father’s trauma. Furthermore, the identification that can be obtained is that the loss that Ali feels is the loss of an "ambiguous" mother figure. Ali is looking for the mother he hoped for in the past according to the description given by his father. However, Ali did not find this mother figure as he found another mother figures that had changed due to the social factors she experienced. In the end Ali interprets that mother is not a figure, mother is a feeling of affection and a sense of belonging. Until finally Ali found what he was really looking for, namely a mother who was reflected through his aunts and a mother who represented affection and belonging which also came from the aunts who met Ali in New York.